Teaching Counseling Microskills to Audiology Students: Recommendations from Professional Counseling Educators - Beck, Kelly; Kulzer, Jamie (Seminars in Hearing, 2018)
To provide the highest quality services, audiologists incorporate counseling into their professional practice. This article, written by professional counselors, highlights the distinction between services provided by professional counselors (i.e., psychotherapy) and counseling microskills used by all health and rehabilitation professionals. Effective application of counseling microskills facilitates a strong therapeutic alliance, which research shows contributes to positive therapeutic outcomes. Counseling microskills should be taught early in graduate programs, because they serve as the foundation for the therapeutic alliance and allow for more effective application of other therapeutic interventions. The four most critical counseling microskills for audiologists are active listening, nonverbal communication, silence, and empathy. These skills should be taught using experiential learning activities (i.e., classroom role-play and use of simulated patients) that incorporate practice, repetition, and feedback. Students should be evaluated on their ability to perform counseling microskills using a detailed grading rubric. Instructors should deliver feedback on these skills with care to reduce potential negative reactions. Ultimately, effectively teaching counseling microskills in graduate programs can improve students' ability to facilitate the therapeutic alliance and facilitate better health outcomes for patients.
Keywords: Scope of practice; counseling; microskills; teaching methods; evaluation